Chronicle of the International Congress "La critique génétique comme processus" (Paris, 17th 20th October 2018) (Prassi Ecdotiche della Modernità Letteraria, 2019)
The ITEM, Instut des Textes et Manuscrits Modernes, celebrated 50 years of activity with a major congress held in Paris from 17th to 20th October 2018: "La critique génétique comme processus". The meeting offered the opportunity to retrace the history of the Parisian laboratory, cradle of the critique génétique, and to draw up a balance of 50 years of activity.